M-TOR inhibitors in the treatment of advanced renal cell carcinoma - Stec, Rafał; Mączewski, Michał; Smoter, Marta; Bodnar, Lubomir; Szczylik, Cezary (Contemporary Oncology/Współczesna Onkologia, 2011)
Renal cell cancer (RCC) accounts for approximately 3% of all registered malignancies in Poland. According to the most recent National Cancer Register, 2283 men and 1483 women were diagnosed with renal cancer in 2006. Up to 30% of patients with RCC present with metastatic disease. M-TOR inhibitors became a new therapeutic option for patients with metastatic RCC. Two of them, temsirolimus and everolimus, are currently approved for clinical use for patients with advanced renal cancer. Anticancer activity of m-TOR inhibitors is related to cellular cycle regulation and inhibition of uncontrolled angiogenesis. Based on clinical trials, temsirolimus is indicated as the first line of chemotherapy for patients with at least three poor prognostic factors. Everolimus should be administered as the second line of treatment, for patients who relapsed after antiangiogenic therapy.